Case Study : Chemical, Functional and Sensory Characteristics of Instant Savory Rice compared with Instant White Rice (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Variations of processing rice into cooked rice had long been developed. One of the rice products that has been widely circulated in the community is savory rice. Savory rice with instant processing was more practical in serving. This research aimed to determine the physical, chemical, functional, and sensory characteristics of instant savory rice compared to instant white rice. The stages of processing instant savory rice include washing, soaking, cooking, freezing, and drying. The freezing process was carried out at -20 °C for 24 h. The drying process for instant savory rice uses a fluidized bed dryer for 3 h. Instant white rice was used as a control. Instant savory rice contains moisture content (8.48%), ash content (3.93%), fat content (5.56%), protein content (7.54%), and starch digestibility (54.84%) which was higher than instant white rice. Instant savory rice has carbohydrate content (82.97%), amylose content (32.39%), amylopectin content (46.59%), starch content (79.98%), and resistant starch content (1.90%) lower than instant white rice. In terms of sensory test results revealed that instant savory rice after rehydration was preferred by consumers compared to instant white rice regarding color, aroma, taste, texture, and overall with a score of 5.39-5.84.